2014
DOI: 10.2136/sssaj2013.12.0511
|View full text |Cite
|
Sign up to set email alerts
|

How Tree Encroachment and Soil Properties Affect Soil Aggregate Stability in an Eroded Grassland in South Africa

Abstract: Gully erosion and woody plant encroachment are frequently observed in grasslands worldwide. Soil aggregate stability is one of the drivers of gully erosion and needs to be studied, especially in the context of both tree encroachment and gully erosion. This study compared the effects of tree encroachment [paperbark thorn; Vachellia sieberiana (DC.) Kyal. & Boatwr. previously called Acacia sieberiana DC.] and soil surface horizon properties on the aggregate stability (as measured by mean weight diameter, MWD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
3
10
2
Order By: Relevance
“…The low structural stability of the BC horizon in both the Lixisol and Luvisol profiles is associated with the presence of interstratified illite-smectite minerals, confirming its occurrence as reported in a study of the base of active dongas in the same area (Podwojewski et al, 2014). Singer et al (1992) found that the shrinking and swelling that accompanies drying and wetting of smectite decreases aggregate stability, because the clay is more readily separated from the aggregates.…”
Section: Lateral Extension Of Gulliessupporting
confidence: 79%
See 3 more Smart Citations
“…The low structural stability of the BC horizon in both the Lixisol and Luvisol profiles is associated with the presence of interstratified illite-smectite minerals, confirming its occurrence as reported in a study of the base of active dongas in the same area (Podwojewski et al, 2014). Singer et al (1992) found that the shrinking and swelling that accompanies drying and wetting of smectite decreases aggregate stability, because the clay is more readily separated from the aggregates.…”
Section: Lateral Extension Of Gulliessupporting
confidence: 79%
“…This suggests that slaking of aggregates in the surface horizon of the non‐degraded area is minimal. This structural stability is mostly maintained by the fine roots of the complete grass cover (Podwojewski et al ., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Roots may influence the soil hydrological features by forming macropores within the soil and controlling the infiltration rate and movement of water; thus, the roots drive the soil moisture content (Ziegler & Giambelluca, 1998;Bernini et al, 2003;Vergani & Graf, 2015). Likewise, roots improve the soil structure and, thereafter, enhance the stability of soil aggregates: this effect is of upmost importance to limit the soil erosion and to allow the establishment of a permanent vegetation cover (Burri et al, 2009;Podwojewski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%